2008
DOI: 10.4049/jimmunol.181.10.6789
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Early Expansion and Maturation of Semi-Invariant NK T Cells Inhibited Autoimmune Pathogenesis in Congenic Nonobese Diabetic Mice

Abstract: Semi-invariant NK T cell (iNKT) deficiency has long been associated with the pathogenesis of type 1 diabetes (T1D), but the linkage between this the deficiency and T1D susceptibility gene(s) remains unclear. We analyzed NOD mice subcongenic for resistant alleles of Idd9 locus in search for protective mechanisms against T1D, and found that iNKT cell development was significantly enhanced with a more advanced mature phenotype and function in mice containing Idd9.1 sublocus of B10 origin. The enhanced iNKT cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Previous linkage studies and congenic analyses reported by others and us identified genetic loci on Chr 1, 2, and 4 that reduce iNKT-cell development in NOD mice 2226, 28, 44 . Compared to the previous linkage studies, the splenic QTL on Chr 1 (peaks at 172.96Mb) identified here overlaps with the Nkt1 locus that contains Slamf1 and Slamf6 genes known to regulate iNKT-cell development 27, 29 .…”
Section: Discussionmentioning
confidence: 71%
“…Previous linkage studies and congenic analyses reported by others and us identified genetic loci on Chr 1, 2, and 4 that reduce iNKT-cell development in NOD mice 2226, 28, 44 . Compared to the previous linkage studies, the splenic QTL on Chr 1 (peaks at 172.96Mb) identified here overlaps with the Nkt1 locus that contains Slamf1 and Slamf6 genes known to regulate iNKT-cell development 27, 29 .…”
Section: Discussionmentioning
confidence: 71%
“…To date, the best studied example of this association is T1D in NOD mice. Increasing numbers of NKT cells in NOD mice by adoptive transfer (45,46), congenesis (35,36,39,47), transgenic expression of the Va14Ja18 TCR a-chain (48) or CD1d (49), or by stimulating them with a-GalCer (50, 51) all inhibit the onset of T1D. Furthermore, T1D was accelerated in NOD.Cd1d 2/2 mice, which completely lack NKT cells (52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…Although the genes localized at Idd9.1 are unknown, they are associated with increased B-cell pathogenic activity [23], low numbers of induced iNKT cells [invariant NKT cells (natural killer T-cells)] and reduced T reg cell (regulatory T-cell) development and activity in NOD mice [24,25]. Candidate susceptibility genes at Idd9.2 and Idd9.3 encode CD30, TNFR2 (tumour necrosis factor receptor 2) and CD137 respectively [22].…”
Section: The Nod Mouse Model Geneticsmentioning
confidence: 99%